Tanggung Jawab Saksi Pengenal Terhadap Keterangan yang Diberikan dalam Pembuatan Akta Autentik - Dirgantara, Pebry (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 4 No 2 (2019)DO - 10.24843/AC.2019.v04.i02.p03, 2019)
Identifying witness is a person who introduces the identity of the person to the notary. Identifying witnesses are also needed in making deeds if the parties have advanced age or have weak memory. In UUJN-P Article 40 paragraph (2) only states the conditions can be a witness in the deed. In Article 39 of the UUJN-P it is not explained about the position of the witnesses and the responsibility of the witnesses to the truth of the information regarding the identities of the viewers, in this case it can be said as the obscurity of legal norms. This study uses a normative juridical research method. The approach used in this study is through the law approach (statue approach), conceptual approach (conceptual approac) and case approach (case approach). The legal material collection technique is through library research relating to identifying witnesses in making authentic deeds. The techniques for analyzing legal materials used are description, interpretation, and argumentation. The position of the identifying witness is the person who introduces the notary to the viewer. The witness present here has a role in making authentic deeds as the person who introduces the applicants to the notary. The duty of the identifying witness is to introduce the viewers based on the identity of the viewer in the form of a valid National Identity Card. The witness here is not responsible for the contents of the authentic deed. Identifying witnesses can be held criminally responsible if they deliberately provide false information to the notary regarding the identity of the viewers in the process of making a deed. The criminal witness given to the witness is an criminal sanction in the form of a prison. Can ask for accountability because the witness is the person who first introduced the viewers to the notary and there are elements of error, the element of loss and the existence of elements of cause and effect. Pihak yang memperkenalkan identitas dari para penghadap kepada notaris disebut sebagai saksi pengenal. Saksi pengenal juga diperlukan dalam pembuatan akta apabila para pihak sudah berumur lanjut atau sudah memiliki daya ingat yang lemah.  Dalam UUJN-P Pasal 40 ayat (2) menentukan syarat saksi pengenal pada akta. Pasal 39 UUJN-P tidak menerangkan kedudukan dan tanggungjawab saksi pengenal. Penelitian yuridis normatif merupakan metode yang digunakan dalam penelitian ini. Pada penelitian ini menggunakan pendekatan undang-undang (statue approach), pendekatan konseptual (conceptual approach) dan pendekatan kasus (case approach). Adapun teknik pengumpulan bahan hukum yang digunakan yakni berdasarkan teknik kepustakaan yang berhubungan dengan saksi pengenal dalam pembuatan akta autentik. Teknik deskripsi, interprestasi serta argumentasi merupakan teknik analisis bahan hukum yang diterapkan dalam penelitian ini. Kedudukan dari seorang saksi pengenal dalam suatu akta autentik yakni sebagai pihak yang memperkenalkan para pihak sebagai penghadap kepada notaris, maka dapat dikatakan seorang saksi pengenal mempertegas keterangan yang diberikan oleh penghadap kepada notaris. Dapat dikatakan saksi pengenal memiliki tugas untuk memperkenalkan para penghadap sesuai dengan Kartu Tanda Penduduk yang berlaku. Terhadap isi akta yang dibuat, saksi pengenal tidak memiliki tanggung jawab. Pertanggungjawaban saksi pengenal secara pidana hanya dapat dikenakan apabila ia memberikan keterangan palsu terhadap identitas para penghadap. Saksi pidana yang diberikan kepada saksi pengenal adalah sanksi pidana berupa penjara dikarenakan saksi pengenal disini yang dianggap lebih mengetahui identitas dari penghadap.